2012
DOI: 10.1136/medethics-2011-100119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the demand for ‘proxy assent’ on recruitment to a randomised controlled trial of vaccination testing in care homes

Abstract: Legal frameworks are in place to protect those who lack the capacity to consent to research, such as the Mental Capacity Act in the UK. Assent is sought instead from a proxy, usually a relative. However, the same legislation may, perversely, affect the welfare of those who lack capacity and of others by hindering the process of recruitment into otherwise potentially beneficial research. In addition, the onus of responsibility is moved from those who know most about the study (ie, the scientific community) to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…There were 24 studies which reported challenges that fall under this theme [ 27 29 , 31 33 , 35 37 , 39 42 , 44 , 50 55 , 57 , 59 , 61 , 62 ]. Some major issues included in this theme were: recruitment, consent, residents prefer treatment over placebo, and attrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 24 studies which reported challenges that fall under this theme [ 27 29 , 31 33 , 35 37 , 39 42 , 44 , 50 55 , 57 , 59 , 61 , 62 ]. Some major issues included in this theme were: recruitment, consent, residents prefer treatment over placebo, and attrition.…”
Section: Resultsmentioning
confidence: 99%
“…Obtaining informed consent from LTC residents, including cognitively impaired and emotionally unstable candidates, was described as difficult and time consuming [ 28 , 40 , 50 , 54 , 59 ]. Residents’ ability to consent could change during the research period, and some were excluded unnecessarily due to incorrect evaluations of their ability to consent [ 40 , 51 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there are significant differences under these two separate regulatory regimes in the provisions for those lacking capacity to participate in medical research (Table 1). These differences increase the burden on researchers and clinicians responsible for recruiting eligible participants which presents additional barriers to conducting research with vulnerable groups [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the current legal framework, its legislative differences and uncertainty surrounding their interpretation has resulted in confusion both for researchers and Research Ethics Committees,5 6 as well as clinicians, relatives and carers involved in decisions about adults lacking capacity participating in research 7. These differences increase the burden on those involved in making decisions about research participation and present barriers to conducting research with individuals with cognitive impairments 8 9. As a result, the exclusion of these groups from research is widespread, and concerns about their exclusion have been reported 10 11.…”
Section: Introductionmentioning
confidence: 99%